Interventions to promote healthy nutrition and lifestyle and to tackle overweight and obesity amongst children in need in Europe: a rapid literature review - Anela Halilagic; Renos Roussos; Matzourana Argyropoulou; Vaios Svolos; Vaios Svolos; Christina Mavrogianni; Odysseas Androutsos; Theodora Mouratidou; Theodora Mouratidou; Yannis Manios; Yannis Manios; George Moschonis; et al. (Frontiers in Nutrition)
IntroductionThe global prevalence of overweight and obesity has reached epidemic proportions amongst children and adolescents, with approximately one third of children in Europe being overweight or obese. There is a higher likelihood for overweight and obesity reported for vulnerable groups of children, also known as children in need. As there is currently no knowledge of the best practice interventions for improving nutrition and physical activity habits amongst these vulnerable groups, the aim of this rapid review was to examine evidence that focused on best practice interventions to tackle overweight and obesity in children in need in Greece and/or other European countries.MethodsStudies were sought that presented methods and results of interventions and their evaluation. There were 989 results originally identified from database searches, which then reduced to 8 studies for inclusion following abstract and full-text screening processes. A narrative synthesis was conducted to present the characteristics and results of each study.ResultsThe only group of children in need that was identified was of low socioeconomic status (SES). There were several interventions identified that were successful across various countries in Europe, however there is a lack of best practice interventions to contribute to longer lasting solutions to preventing overweight and obesity.ConclusionOur findings encourage the implementation of interventions that will be inclusive of children with vulnerabilities other than low SES, as well as the establishment of specific criteria guiding the design of best practice interventions.